Nomenclatural and taxonomical novelties in southamerican Glandularia (Verbenaceae) - O’leary, Nataly; Peralta, Paola; Múlgura, Maria Ema (Phytotaxa, 2013)
In this work, a lectotype for a Chamisso’s species is designated, two new synonyms within Glandularia are proposed, and a distributional misleading remark is clarified.